Deer Browsing Increases Stem Slenderness and Crown Irregularity and Modifies the Effects of Light Gradients on Architecture of Forest Tree Saplings - Cecilia Cacciatori; Anna Gazda; Jan Bodziarczyk; Kacper Foremnik; Aklilu B. Madalcho; Zbigniew Maciejewski; Remigiusz Pielech; Andrzej Tomski; Antoni Zięba; Tomasz Zwijacz‐Kozica; Jerzy Szwagrzyk (Ecology and Evolution)
ABSTRACT Browsing by ungulates is commonly assumed to target the upper parts of sapling crowns, leading to reduced vertical growth or even growth cessation. However, the extent to which browsing induces shifts in resource allocation toward lateral growth remains unclear. This study explores the impact of browsing intensity (BI) and light availability on the architectural traits of six temperate tree species, focusing on height‐diameter ratio (H/D), crown slenderness (CL/CW), and crown irregularity (CI) across sapling height classes. Browsing pressure and architectural responses varied across height groups, reflecting diverse adaptive strategies. BI was weakly but negatively correlated with sapling height, indicating that even tall saplings (> 2 m) experience browsing, particularly in the lower crown. H/D consistently increased with BI across all height classes, with stronger effects in medium and tall saplings. Light influenced H/D differently between browsed and unbrowsed saplings: unbrowsed saplings showed reduced H/D only under high light conditions, while browsed saplings exhibited consistent reductions regardless of light levels. CL/CW was negatively but insignificantly affected by BI. Light increased CL/CW in unbrowsed saplings across all height classes but decreased it in browsed short and medium saplings, suggesting a ‘pruning’ effect of browsing that altered competition dynamics. Species‐specific analysis of Fagus sylvatica revealed an increase in CL/CW with BI, reflecting unique adaptive responses. CI increased significantly with BI across all height classes, with the strongest effects in medium and tall saplings. Light reduced CI in browsed short saplings but had inconsistent effects on unbrowsed individuals. Variation partitioning showed that light explained most variation in H/D and CL/CW for shorter saplings, while BI predominantly influenced CI in taller ones. By integrating the effects of browsing and light, this study provides insights into juvenile tree adaptations and resilience under ecological stressors, advancing our understanding of tree growth strategies in challenging environments.